Soil Chemical Properties and Soybean Yield Due to Application of Biochar and Compost of Plant Waste - Junita Barus (UNIVERSITY OF LAMPUNG, 2016)
The importance to return organic matter to the soil has been widely recognized, especially to agricultural lands that are low in organic matter and nutrients contents that will decrease the productivity of food crops. This study aimed to study the effect of biochar (rice husk and corn cob biochar) and straw compost on soil chemical properties and yield of soybean (Glycine max (L.) Merr. The experiments were done in the laboratory and the field experiment at February–July 2015. The first study was laboratory test using a randomized block design with three replicates. Soil samples were ground and sieved to obtain the less than 4 mm fraction for the incubation experiment. A five kg soil was mixtured with amandement treatments (A: control; B: Rice husk biochar 10 Mg ha-1 ; C: corn cob 10 Mg ha-1; D: straw compost 10 Mg ha-1; and E. Rice husk biochar 10 Mg ha-1 + straw compost 10 Mg ha-1 ; F. corn cob biochar 10 Mg ha-1 + straw compost 10 Mg ha-1) were filled into plastic pots. The treatments were incubated for 1 and 2 months. Soil samples measured were pH, Organic-C, Total-N, P2O5 (Bray-1), K2O (Morgan), Na, Ca, Mg, S, and CEC. The field experiment was conducted at Sukaraja Nuban Village, Batanghari Nuban sub district, East Lampung Regency. The treatments (similar too laboratory experiment) were arranged in a randomized block design with four replicates. Plot size was 10 m × 20 m, and soybean as crop indicators. The parameters observed were plant heigh, number of branches , number of pods per plant , number of seeds per plant, grain weight, and stover. The results of laboratory experiment showed that application of biochar and compost improve soil fertility due to the increase in soil pH and nutrient availability for plant especially P2O5 and K2O available. The treatment of a rice husk biochar and compost mixture was better than single application to improve soil fertility and soybean yield. Apllication mixture husk biochar 10 Mg ha-1and straw compost 10 Mg ha-1 increased grain weight about 41% compost to control.Keywords: Biochar, compost, crop waste, soil chemical properties [How to Cite: Junita B, Dermiyati and H Sudarsono. 2016. Soil Chemical Properties and Soybean Yield Due to Application Biochar and Compost of Plant Waste. J Trop Soils 21: 1-7. Doi: 10.5400/jts.2015.21.1.1]